Examples of the use of GPR for research at airports - Adam Szynkiewicz (Przegląd Komunikacyjny)
Abstract: The GPR tests were carried out for the needs of the expansion of the "Fryderyk Chopin" airport in Okęcie in Warsaw. There were old and new surfaces at the airport. GPR profiling was conducted on selected lines. For the purposes of the research, core drillings and ground core drillings were performed in the airport pavements. The geological interpretation of the GPR data was made on the basis of drilling data. 6 GPR models were developed for the tested airport pavements. The results of each GPR cross-sectional line were compared with the results of the HWD study. It was found that the use of the non-destructive GPR method for monitoring airport pavements causes: reduction of the number of drilling in pavements, minimization of interruptions in aircraft traffic, quick and effective monitoring of the condition of airport pavements. Keywords: GPR; Airport surfaces